(untitled) (Applied Biological Research, 2025)
Colon cancer is the 3rd most prevalent cancer globally, presenting significant epidemiological and economic challenges. Natural products have shown promise as effective alternatives to chemotherapy. The present study was aimed to study the anticancer potential of rat’s ear (Commelina forskaolii) on HT-29 colon cancer cells, focusing on cytotoxic activity, antioxidant potential, and underlying molecular mechanisms. The cytotoxic activity of the ethanolic extract of C. forskaolii was assessed by measuring IC₅₀ value on HT-29 cell lines, enzymatic antioxidant potential and heme oxygenase activity. Gene expression and cell cycle analyses were performed to explore molecular mechanisms. The extract demonstrated significant cytotoxic activity with an IC₅₀ value of 27.4 ± 0.25 μg mL⁻¹. Cell cycle analysis showed that C. forskaolii effectively arrested the cells at G₀/S phase. Additionally, the study revealed an increase in lipid peroxidation and intracellular iron accumulation, leading to the formation of lipid-iron radicals and triggering ferroptosis. Heme oxygenase-1 (HO-1) was found to regulate cellular iron levels and reactive oxygen species (ROS) generation, where moderate HO-1 activity offered cytoprotection, but excessive activity in cancer cells led to oxidative cell death. The findings suggest that C. forskaolii may serve as a valuable natural treatment for colon cancer, targeting oxidative processes that induce cancer cell death and anticancer activity.